Language issues in Saint Vincent and the Grenadines - Prescod, Paula (Varieties of English around the world. General series ;, 2015)
Languages of the Caribbean are fascinating and have been studied extensively. It is a particularly fertile ground for the study of pidgins and creoles and the interplay of language and culture and society. However, the languages of St Vincent and the Grenadines have not received the comprehensive attention they deserve. Because the work accomplished has been published in a wide variety of sources the literature is difficult to locate. Despite the existence of Linguistics and Language Behavior Abstracts (the primary bibliographic resource in the field of linguistics) the linguistics lite.